Evaluating whole-body vibration exposure and neck pain disability among university bus drivers in Selangor - Alias, Ayuni Nabilah; Mustafa Udin, Nurulain; Mohd Fadzil, Farah Farzana (Faculty of Management Sciences, Yala Rajabhat University, 2024)
Vibration is referred to every regular movement a body produces in relation to a fixed point. Bus drivers are exposed to vibration from the movement of the vehicles on the road, which also vibrates the driver's body and the bus seat. The level of WBV that drivers are exposed to in their daily lives is impacted by several factors, such as the bus's design, its speed, the condition of the road, and the driver's position. As a result of their exposure to vibration, bus drivers are consequently at risk for Musculoskeletal Disorders (MSDs) related to low back pain, neck pain, sciatica, and disorders like decreased motor function. This study provides insights on the exposure of whole-body vibration among bus drivers and the prevalence rate of self-reported neck pain symptoms linked to this exposure among university bus drivers. Daily exposure level A (8) for both trips, route J (N=6) and route K (N=6) was found ranging between 0.341 ± 0.107 m/s2 to 0.485 ± 0.008 m/s2, while vibration dose value (VDV) was between 4.264 ± 0.115 m/s1.75 to 6.184 ± 0.106 m/s1.75 for both trips, respectively. Vibration exposure, A (8) and VDV for both routes were recorded below the Exposure Limit Value (ELV) of international standard ISO 2631-1:1997 and Health Guidelines Caution Zone (HGCZ). The mean of neck pain disability index value of 0.163 ± 0.109 for 45 bus drivers. A mean value of 0.118 ± 0.075 indicates the minimum disability for 75% (N= 34) of the drivers. Overall, control measures can be implemented to avoid unnecessary exposure of vibration in future among bus drivers such as regular maintenance services and installation of air seat suspension technology to the driver seat.